Pengaruh Disiplin Kerja, Gaya Kepemimpinan Dan Motivasi Kerja Terhadap Kinerja Pegawai (Study Kasus Dinas Perindustrian Dan Perdagngan Provinsi Sumatera Utara) - Fitri Wulandari; Eka Purnama Sari (Pusat Riset dan Inovasi Nasional, 2023)
The purpose of this study was to determine and analyze the effect of work discipline, leadership style and work motivation on employee performance, to determine and analyze the effect of work discipline, leadership style and work motivation on employee performance at the Department of Industry and Trade of North Sumatra Province. The approach used in this study were all employees of the Department of Industry and Trade of North Sumatra Province, totaling 160 employees. While the samples that meet the sampling criteria for observations made are 62 respondents using the Slovin formula. The data collection technique in this study uses a questionnaire technique and technical data analysis in this study uses the SPSS version 25.00 software program. Partially it is known that work discipline has no positive and significant effect on the performance of the employees of the North Sumatra Province Industry and Trade Office. Partially it is known that motivation has a positive and significant influence on the performance of the employees of the Department of Industry and Trade of North Sumatra Province. Simultaneously it is known that work discipline, leadership style and work motivation have a significant influence on the performance of the employees of the Department of Industry and Trade of North Sumatra Province.